Reduction of Anxiety Through Islamic Spiritual Mindfulness Based on Breathing Exercise in Hypertensive Patients - Mustajidah, Mustajidah; Nurhayati, Nurhayati; Muhaimin, Toha; Anwar, Syamsul; Basri, Achmad Ali (Indonesian Journal of Global Health Research, 2023)
The prevalence of hypertension sufferers in the Serpon 2 Community Health Center working area is 96 people, 37,5 % experience anxiety.Research Objectives. To find out the influence of Islamic spiritual mindfulness based on breathing exercise on anxiety in hypertensive patients. Research Method. Quasi-experimental research design. The population was all hypertensive patients and a sample of hypertensive patients with anxiety in the working area of Serpong 2 Community Health Center, South Tangerang city. The sampling method is purposive sampling with sample 36 Respondent. The data collection tool is the HARS instrument. Research Results. Islamic Spiritual Mindfulness based on Breathing Exercise has an influence on anxiety in Hypertension patients with a significance p value = 0.000 Conclusion. Islamic Spiritual Mindfulness based on Breathing Exercise is effective in reducing anxiety. Conclusion Islamic Spiritual Mindfulness based on breathing exercise deserves to be a complementary therapy or non-pharmacological therapy to reduce anxiety in hypertensive patients.